A review of the potential occupational health and safety implications of nanotechnology - Australia. Safety and Compensation Council (Canberra, 2006)
"This review of the literature explores the occupational health and safety concerns of the nascent nanotechnology industry in Australia. The primary focus is on human exposure factors and the toxicology of nanoparticles engineered for either commercial or research use."